2015
DOI: 10.1016/j.nanoen.2015.07.003
|View full text |Cite
|
Sign up to set email alerts
|

18.5% efficient graphene/GaAs van der Waals heterostructure solar cell

Abstract: Lin, 18.5% Efficient graphene/GaAs van der Waals heterostructure solar cell, Nano Energy, http://dx.Abstract: High efficient solar cell is highly demanded for sustainable development of human society, leading to the cutting-edge research on various types of solar cells. The physical picture of graphene/semiconductor van der Waals Schottky diode is unique as Fermi level of graphene can be tuned by gate structure relatively independent of semiconductor substrate. However, the reported gated graphene/semiconducto… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
86
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(93 citation statements)
references
References 61 publications
3
86
0
Order By: Relevance
“…From the simulations, it also noticed that the intermediate structures (i.e., trapezoidal-and parabolic-shaped), the light reflection loss is lower than the rectangular shaped nano-grating structure but higher than the triangular-shaped nano-grating structure. The simulated results confirm that the reduction of light reflection losses will increase the conversion efficiency significantly in GaAs solar cells can be correlated to a practical example of higher conversion efficiency achieved in thin layer dielectric-coated graphene/GaAs solar cells [12]. Therefore, it has confirmed that the triangular (i.e., conical or perfect cone)-shaped nano-grating structures are an excellent alternative antireflective (AR) coating for the reduction of light reflection losses and improve the conversion efficiency in GaAs solar cells for a sustainable future.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…From the simulations, it also noticed that the intermediate structures (i.e., trapezoidal-and parabolic-shaped), the light reflection loss is lower than the rectangular shaped nano-grating structure but higher than the triangular-shaped nano-grating structure. The simulated results confirm that the reduction of light reflection losses will increase the conversion efficiency significantly in GaAs solar cells can be correlated to a practical example of higher conversion efficiency achieved in thin layer dielectric-coated graphene/GaAs solar cells [12]. Therefore, it has confirmed that the triangular (i.e., conical or perfect cone)-shaped nano-grating structures are an excellent alternative antireflective (AR) coating for the reduction of light reflection losses and improve the conversion efficiency in GaAs solar cells for a sustainable future.…”
Section: Discussionsupporting
confidence: 67%
“…This type of nano-grating or nano-rod structure performs as a single layer AR coating, whereas the triangular (such as, conical or perfect cone) and parabolic shaped nano-grating structures are performing as a multilayer broadband AR coating [3][4][5][6][7][8]. There are some other reports found in the literature related to improving the optical gain in solar cell systems, including surface plasmon resonance-based multilayer structures and also a new design of GaAs solar cells [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The relative permittivity of the dielectric particle is ε r , and the relative permeability is µ r = 1. This kind of structure can be realized experimentally by using wet transfer technique similar with fabrication of graphene/GaAs heterostructure [49] and graphene can be well grown by CVD reaction between CH 4 and H 2 on cooper substrate, which can be etched away using acid solution. The suspending graphene can be transferred to arbitrary substrate subsequently.…”
Section: Structure and Modelmentioning
confidence: 99%
“…A more expensive graphene/GaAs Shottky junction solar cell with an efficiency of >18% has been reported [24]. These values of efficiency are the best ones for graphene-based solar cells.…”
mentioning
confidence: 97%
“…properly optimizing the cell configuration, the efficiency has been improved up to 15.6% [23]. A more expensive graphene/GaAs Shottky junction solar cell with an efficiency of >18% has been reported [24]. These values of efficiency are the best ones for graphene-based solar cells.…”
mentioning
confidence: 99%